Ontology of Literacy in the Workplace: A Phenomenological Perspective - Wily Ariwiguna; Anas Ahmadi; Syamsul Sodiq; Mohammad Rokib (Universitas Muhammadiyah Gorontalo, 2025)
This study explores the ontological essence of workplace literacy through a phenomenological lens, addressing the evolving demands of modern professional environments that require advanced competencies in literacy, numeracy, and critical thinking. Grounded in the recognition that contemporary workplaces are increasingly complex and text-mediated, this research investigates how reading, writing, and communication practices are enacted, experienced, and interpreted by employees across various sectors in Indonesia. Employing transcendental phenomenology as the methodological framework, the study systematically analyzes both the textural descriptions and structural essences of informants' lived experiences from diverse workplace settings. This dual analysis reveals that literacy exists and manifests within professional contexts as more than just a technical skill. The findings demonstrate that workplace literacy operates simultaneously as a functional competency and as a form of professional consciousness that mediates relationships among individuals, texts, and organizational systems. Literacy emerges as essential for maintaining work consistency, enabling critical self-reflection, and bridging personal values with organizational culture. Furthermore, the study reveals that authentic workplace literacy is deeply rooted in reflective awareness and humanistic values, rather than being confined to instrumental or procedural applications. These insights underscore the necessity of cultivating workplace literacy development programs that prioritize reflexive practice, critical consciousness, and the integration of human-centered values within organizational learning frameworks, ultimately contributing to more meaningful and effective professional communication practices.